COMMUNICATIVE FOREIGN LANGUAGE TEACHING OF FUTURE ENGINEERS - Chevychelova, O.; Чевичелова, О. О.; Чевычелова, Е. А. (Харьковский национальный автомобильно-дорожный университет, 2017)
The essence of communicative approach to foreign language teaching has been defined; the conditions for developing communicative competence of future engineers at higher school have been described. The importance of stimulating the cognitive interest has been grounded and the ways of creating communicative situations at foreign language classes at higher technical school have been considered.
КОМУНІКАТИВНО-ОРІЄНТОВАНЕ НАВЧАННЯ ІНОЗЕМНОЇ МОВИ МАЙБУТНІХ ІНЖЕНЕРІВ
КОММУНИКАТИВНО-ОРИЕНТИРОВАННОЕ ОБУЧЕНИЕ ИНОСТРАННОМУ ЯЗЫКУ БУДУЩИХ ИНЖЕНЕРОВ
Keywords: higher technical school; foreign language; competence; communicative approach; іноземна мова; компетенція; комунікативний підхід; иностранный язык; компетенция; коммуникативный подход; 378.147